General practitioners with a special interest in respiratory medicine: national survey of UK primary care organisations - Price David; Netuveli Gopalakrishnan; Pinnock Hilary; Sheikh Aziz (BMC, 2005)
Abstract Background To meet the universally recognised challenge of caring for people with long-term diseases many healthcare cultures are encouraging family physicians to develop specialist skills. We aimed to determine the major factors influencing the appointment of respiratory General Practitioners with a Special Interest (GPwSI) in the UK, and to determine the priority attached to the potential roles, perceived barriers to implementation, and monitoring planned. Methods We sent a piloted semi-structured questionnaire to a random sample of 50% of English and Welsh primary care organisations (PCOs) (n = 161) during winter 2003. In addition to descriptive statistics, we used hierarchical cluster analysis to classify service priorities. Free-text responses to open-ended questions were analysed qualitatively by a multidisciplinary group to identify emerging themes. Results Of the 111 (69%) PCOs who responded, 7 (6%) already have, and a further 35 (32%) are planning, a respiratory GPwSI service. This proportion is considerably lower than in specialities linked to National Health Service clinical priorities. Local needs and pressure on hospital beds were the main described motives for developing a service. Stated service priorities were to relieve pressure on secondary care and to improve quality of care, including the strategic planning of respiratory services within PCOs. Conclusion The relatively few respiratory GPwSIs currently in post reflects the lack of government prioritisation of respiratory care. However, respiratory GPwSI services are increasingly being considered as a local strategy for reducing pressure on secondary care respiratory services and raising standards of chronic disease management in primary care.